Transcriptomic and metabolomic analyses of the ovaries of Taihe black-bone silky fowls at the peak egg-laying and nesting period - Xiang, Xin; Huang, Xuan; Wang, Jianfeng; Zhang, Haiyang; Zhou, Wei; Xu, Chunhui; Huang, Yunyan; Tan, Yuting; Yin, Zhaozheng (Frontiers in Genetics, 2023)
The poor reproductive performance of most local Chinese chickens limits the economic benefits and output of related enterprises. As an excellent local breed in China, Taihe black-bone silky fowl is in urgent need of our development and utilization. In this study, we performed transcriptomic and metabolomic analyses of the ovaries of Taihe black-bone silky fowls at the peak egg-laying period（PP） and nesting period（NP） to reveal the molecular mechanisms affecting reproductive performance. In the transcriptome, we identified five key differentially expressed genes(DEGs) that may affect the reproductive performance of Taihe black-bone silky fowl: BCHE, CCL5, SMOC1, CYTL1, and SCIN, as well as three important pathways: the extracellular region, Neuroactive ligand-receptor interaction and Cytokine-cytokine receptor interaction. In the metabolome, we predicted three important ovarian significantly differential metabolites(SDMs): LPC 20:4, Bisphenol A, and Cortisol. By integration analysis of transcriptome and metabolome, we identified three important metabolite-gene pairs: “LPC 20:4-BCHE”, “Bisphenol A-SMOC1”, and “Cortisol- SCIN”. In summary, this study contributes to a deeper understanding of the regulatory mechanism of egg production in Taihe black-bone silky fowl and provides a scientific basis for improving the reproductive performance of Chinese local chickens.